Combined photodynamic therapy with chloroaluminum phthalocyanine and doxorubicin nanoemulsions in breast cancer model - Cabral, Agata Silva [UNESP]; Rivas Leonel, Ellen Cristina [UNESP]; Candido, Natalia Maria [UNESP]; Piva, Henrique Luis; Melo, Maryanne Trafani de; Taboga, Sebastiao Roberto [UNESP]; Rahal, Paula [UNESP]; Tedesco, Antonio Claudio; Calmon, Marilia Freitas [UNESP] (Elsevier B.V., 2021)
Breast cancer is the most common neoplasm among women but thanks to innovative therapies, patients' prognosis has considerably improved. In this aspect, nanotechnology has been applied for cancer therapy aiming to reduce its usual side effects. In this study we aimed to evaluate the effects of nanoemulsions containing photosensitizer and chemotherapeutic agents associated with photodynamic therapy in a breast cancer in vivo model. Our results showed that synergistic treatments in which chloroaluminum phthalocyanine (NE-Pc) administered together with Doxorubicin (Dox) in the presence of laser irradiation (NE-PcDoxo + PDT) led to a reduction of 4 T1 induced breast cancer in mice, decline of tumor VEGF expression, increase in Caspase-3 expression, tissue necrosis and massive decrease in proliferative cells, as shown by Ki67 immunostaining. Furthermore, this associated treatment induced overexpression of apoptotic genes ABL1, CD70, CRADD, FASL, and NME5 and a reduction in expression of anticancer drug target genes CDK2, ERBB2, FIGF, IGF2, PARP4 and PGR. These results validate this treatment as a promising alternative to improve the currently applied anticancer strategies.
Keywords: Alternative therapy; Anticancer treatment; Breast cancer; Nanotechnology; PDT; Photosensitizer